Crystal structure of the retroviral protease‐like domain of a protozoal DNA damage‐inducible 1 protein. Issue 9 (3rd August 2018) - Kumar, Sushant; Suguna, Kaza
Abstract : DNA damage‐inducible 1 (Ddi1) is a multidomain protein with one of the domains being retropepsin‐like. HIV‐1 protease inhibitors were found to reduce opportunistic infections caused by pathogens like Leishmania and Plasmodium, and some of them were shown to inhibit the growth of these parasites. In Leishmania, Ddi1 was identified as a likely target of the inhibitors. We report the crystal structure of the retropepsin‐like domain of Ddi1 from Leishmania major as a dimer with clear density for the critical 'flap' region. We have characterized binding with one of the HIV‐1 protease inhibitors in solution using bio‐layer interferometry and by docking. Further, we have performed molecular dynamics (MD) simulation studies that show that the protein undergoes a conformational change from open to semi‐open and closed forms with the closing of the flexible flap over the active site. Abstract : We determined the crystal structure of the retroviral protease domain of DNA damage‐inducible 1 protein from Leishmania major ( Lm Ddi1‐RVP). The overall structure is similar to the HIV‐1 protease. However, the flap, an important determinant in substrate/inhibitor binding in HIV‐1 protease, is unstructured and flexible in Lm Ddi1‐RVP, as shown by molecular dynamics (MD) simulation studies that captured various conformational states of the flap.